Alternatives Therapeutic Approaches to Conventional Antibiotics: Advantages, Limitations and Potential Application in Medicine - Hiba Alaoui Mdarhri; Rachid Benmessaoud; Houda Yacoubi; Lina Seffar; Houda Guennouni Assimi; Mouhsine Hamam; Rihabe Boussettine; Najoie Filali-Ansari; Fatima Azzahra Lahlou; Idrissa Diawara; Moulay Mustapha Ennaji; Mohamed Kettani-Halabi (Antibiotics, 2022)
Resistance to antimicrobials and particularly multidrug resistance is one of the greatest challenges in the health system nowadays. The continual increase in the rates of antimicrobial resistance worldwide boosted by the ongoing COVID-19 pandemic poses a major public health threat. Different approaches have been employed to minimize the effect of resistance and control this threat, but the question still lingers as to their safety and efficiency. In this context, new anti-infectious approaches against multidrug resistance are being examined. Use of new antibiotics and their combination with new β-lactamase inhibitors, phage therapy, antimicrobial peptides, nanoparticles, and antisense antimicrobial therapeutics are considered as one such promising approach for overcoming bacterial resistance. In this review, we provide insights into these emerging alternative therapies that are currently being evaluated and which may be developed in the future to break the progression of antimicrobial resistance. We focus on their advantages and limitations and potential application in medicine. We further highlight the importance of the combination therapy approach, wherein two or more therapies are used in combination in order to more effectively combat infectious disease and increasing access to quality healthcare. These advances could give an alternate solution to overcome antimicrobial drug resistance. We eventually hope to provide useful information for clinicians who are seeking solutions to the problems caused by antimicrobial resistance.